1999
DOI: 10.1620/tjem.188.47
|View full text |Cite
|
Sign up to set email alerts
|

Detection of TTV in Peripheral Blood Mononuclear Cells of Intravenous Drug Users.

Abstract: In order to further elucidate the tropism of the novel hepatitis TT virus (TTV) we investigated 22 intravenous drug users (IVDU) for the presence of viral DNA in their peripheral blood mononuclear cells (PBMC) by means of seminested polymerase chain reaction using a set of primers specific for the conserved region of its genome. We detected TTV DNA in 63% of those individuals who had previously been found positive for the agent in their serum, whereas the three remaining ones not displaying TTV DNA in their se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Despite no currently existing culture model for TTV, several data suggest viral replication in PBMCs and lymphocytes (300)(301)(302). TTV DNA has been detected in blood, plasma, cord blood, and PMBCs (58,297,300,(303)(304)(305). In PBMCs and other blood cells, the TTV genome has been detected in monocytes and natural killer cells, as well as in B and T lymphocytes (297,300,303,306).…”
Section: Single-stranded Dna Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite no currently existing culture model for TTV, several data suggest viral replication in PBMCs and lymphocytes (300)(301)(302). TTV DNA has been detected in blood, plasma, cord blood, and PMBCs (58,297,300,(303)(304)(305). In PBMCs and other blood cells, the TTV genome has been detected in monocytes and natural killer cells, as well as in B and T lymphocytes (297,300,303,306).…”
Section: Single-stranded Dna Virusesmentioning
confidence: 99%
“…TTV DNA has been detected in blood, plasma, cord blood, and PMBCs (58,297,300,(303)(304)(305). In PBMCs and other blood cells, the TTV genome has been detected in monocytes and natural killer cells, as well as in B and T lymphocytes (297,300,303,306). TTV has also been detected in bone marrow, spleen (296,307), and other diverse clinical specimens (296,(308)(309)(310)(311)(312)(313)(314)(315)(316)(317).…”
Section: Single-stranded Dna Virusesmentioning
confidence: 99%
“…Peripheral blood mononuclear cells (PBMC) but not red blood cells freshly harvested from infected individuals also harbor TTV DNA (93,118,125,136), suggesting that the virus might replicate in lymphoid cells as well as in hepatocytes. Interestingly, the genotypes of plasma-and PBMC-associated virus sometimes differed in one study (118), suggesting a compartmentalization of TTV infection similar to what was observed for HIV-1 and HCV (91).…”
Section: Interactions With Infected Hostsmentioning
confidence: 99%
“…Most often the highest TTV detection rates have been reported among multitransfused thalassemic subjects, hemodialysis patients, hemophiliacs and intravenous drug abusers. [10][11][12][13]17,40 In addition, it has been detected more often in hepatitis B and C patients than in control groups. 12,17,41 Furthermore, the detection of the virus in commercial blood products also indicates parenteral transmission.…”
Section: Percentage Of Positive Patients In a Category5mentioning
confidence: 99%